Penguatan Moderasi Beragama bagi Mahasiswa Fakultas Syariah UINSI Samarinda: Peran Mahasiswa sebagai Agen Perubahan - Lestari, Yenni Tria; Anisa, Nur; Amrull, Akbar Taufik; Salabi, Agus Salim (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2024)
This research aims to improve students' understanding of the concept of religious moderation and encourage the implementation of its values in daily life. The research method used is action research, which involves cycles of planning, implementation, reflection, and real action. In the planning stage, needs identification was conducted through focus group discussions (FGDs) and interviews to measure students' initial level of understanding. The implementation stage involved the delivery of material by resource persons through interactive lectures, case discussions, and simulations. The reflection stage was conducted through group discussions and individual reflection journals to evaluate students' understanding. Concrete actions are in the form of developing action plans for the implementation of religious moderation values. The results showed a significant increase in student understanding based on pretest and posttest data analysis. Reflections showed that students were able to identify the main challenges of intolerance and committed to organizing interfaith education and dialogue activities. The implications of this study include the importance of experiential participatory approaches in learning religious moderation, which can be applied in other higher education institutions. In addition, the publication of the research results can serve as a reference for the development of similar programs in a broader context.